Jamuro as the Islamic Education Indigenous Psychology Perspective - Syarifan Nurjan; Jony Muhandis; Syamsul Arifin; Maryono Maryono (Al-Hayat: Journal of Islamic Education, 2022)
The religious practice of the Jama'ah Muji Rosul (Jamuro) Surakarta undergoes a process of Sufi life, namely cleansing oneself from the filth of the heart and avoiding low life behaviour to always worship God through tabligh, tahlilan, á¹£alawatan activities and cultural behaviour related to rituals. This study aims to describe diversity and describe the contribution of the Jamaah Muji Rosul worship to Islamic Education. This research study uses a phenomenological approach, describing individual life experiences generally interpreted as concepts or phenomena by exploring phenomena and discussed in indigenous psychology. Data collection through interviews, documentation, observation and analysis of data reduction results are presented in descriptions and conclusions. The results of this study are: (1) religious behaviour based on religious knowledge, belief, and understanding can go hand in hand with the culture of its adherents. Cultural and religious teachings can reinforce each other and behaviour as a form of understanding religion correctly so that it seems as if culture is the teaching of religion itself. Even religious teachings can insert and correct cultural behaviour related to rituals. (2) The educational values in the Book of Mawlid al-BarzanjÃ® Natsr are the selection of educators and a good environment, honesty, sincerity in finding a life partner, age-appropriate education, strong motivation, and the charisma of the native JAMURIC culture of the religious teachings themselves, even the teachings of religion can insert and correct cultural behaviour related to rituals.